Chemical and rheological evaluation of aging characteristics of terminal blend rubberized asphalt binder. (30th April 2019) - Tang, Naipeng; Lv, Quan; Huang, Weidong; Lin, Peng; Yan, Chuanqi
Highlights: FTIR, GPC and rheological master curve were combined to analyze aging behavior. Terminal Blend rubberized asphalt binders offer better long-term aging properties. Terminal Blend hybrid binder has advantage in preserving polymer molecular weight. Polymer molecular weight retention index is promising in evaluating polymer degradation behaviour. Abstract: In the production of terminal blend (TB) rubberized asphalt binder, crumb rubber is digested into asphalt matrix, meanwhile polymers might be added to the degraded rubber/asphalt composite to meet the performance grade criteria. The anti-aging property of TB rubberized asphalt binder is not clear yet. The present study aims to evaluate the aging properties of TB rubberized asphalt binder and TB hybrid binder containing polymeric additive. Fourier transform infrared (FTIR) spectroscopy, Gel permeation chromatography (GPC) and rheological master curve were used to capture the evolution of asphalt binders with aging. The results indicate that TB hybrid binder offers better anti-aging properties than polymer modified asphalt (PMA) with respect to asphalt oxidation and polymer degradation. The presence of nano-silica component in TB rubberized asphalt is considered to improve the anti-aging property. The polymer molecular weight retention index retrieved from GPC test and phase angle difference determined from phase angle master curve are connected with each other. These two methods are very promising in evaluating polymer degradation behavior of PMA.